The Impact of Workplace Stretching on Reduction of Low Back Pain Complaints Among Undip Library Staff - Herna Yunita F Br Ginting; Yuliani Setyaningsih; Suroto Suroto (Health Science Udinus, 2025)
Low Back Pain (LBP) is a musculoskeletal disorder characterized by pain in the lower back. Office workers engaged in prolonged static sitting are at risk of developing LBP, particularly when adopting non-ergonomic positions. A preliminary study on two staff members of the Library Technical Implementation at Diponegoro University (UNDIP) indicated they were at risk of experiencing low back pain. Prolonged sitting with minimal movement causes muscle tension, reduced joint flexibility, and impaired blood circulation in the lower back, triggering LBP onset. This study analyzed the effect of workplace stretching on reducing low back pain complaints among UPT Library staff at UNDIP. Using a quantitative approach with pre-experimental design and total sampling method, all 30 UPT Library staff members participated. Data were collected using the Modified Oswestry Low Back Pain Disability Questionnaire. The Wilcoxon test results showed that workplace stretching interventions significantly reduced low back pain complaints, with p = 0.001. The majority of library staff experienced LBP, with 22 individuals (73.3%) reporting symptoms. Most older respondents suffered from LBP, accounting for 19 individuals (95.0%). Two variables were significantly associated with LBP: age (p = 0.001) and years of service (p = 0.007). Meanwhile, Body Mass Index (BMI) (p = 0.657) and working duration (p = 0.222) showed no significant relationship. The findings demonstrate that workplace stretching is an effective intervention for reducing low back pain among office workers performing prolonged sedentary tasks.